(untitled) (World Economics and Finance Bulletin, 2023)
This article provides that the growing globalization of the manufacturing and financial sectors has radically changed the system of international movement of goods and finance. This process has affected both the availability of foreign financial resources for economically prosperous countries and the need for them. The status of economically developing countries in the system of world trade relations, as well as the pace and structure of global economic growth have significantly affected their demand for external resources, since they are one of the most important factors determining the volume of foreign income and expenditure. As a result, imbalances and imbalances in trade relations lead to a dissonance between demand and availability of foreign financial resources, and subsequently to problems with the inflow of investments.